ANALISIS KESALAHAN EJAAN PADA MAKALAH MORFOLOGI MAHASISWA UNISDA LAMONGAN - Sahputra, Verdyan; Mariyatin; Laila Tri Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the problem of Indonesian spelling errors frequently found in morphology papers written by second-semester students of the Indonesian Language Education Study Program at UNISDA Lamongan. The study aims to describe the forms of spelling errors appearing in students’ academic writing. A descriptive qualitative method was employed, with students’ papers serving as the data source. The data consisted of errors in the use of capital letters, prepositions, punctuation marks, non-standard words, and loanwords. Data were collected through documentation and note-taking techniques and analyzed by identifying, classifying, and describing the errors based on the Indonesian Spelling Guidelines (Pedoman Umum Ejaan Bahasa Indonesia/PUEBI). The results indicate that punctuation errors and the use of non-standard words were the most dominant types of errors. These findings suggest that the errors were mainly caused by students’ limited understanding of Indonesian spelling rules and insufficient accuracy in academic writing. Therefore, improving students’ mastery of spelling conventions is necessary to enhance the quality of academic writing.